Stability of dynamical systems : on the role of monotonic and non-monotonic Lyapunov functions /: on the role of monotonic and non-monotonic Lyapunov functions. (2015) - Michel, Anthony N; Hou, Ling; Liu, Derong, 1963-
No abstract available